Efektivitas Vertical Screw Sebagai Feeder Mangkuk Kotor Pada Mesin Pencuci Mangkuk Ototmatis - Edilla Edilla; Hendriko Hendriko; Daud Suherman (Elektron : Jurnal Ilmiah, 2020)
The bowl feeder is a tool feeder for the process of separating the bowls one by one from the stack arranged vertically and then the bowl will cross the conveyor. Some industries have created screw and pneumatic methods for feeding plastic bowl. However, the existing type of bowl beside plastics there are also ceramics. Ceramic bowl are widely used for culinary. In this final project a bowl feeder device has been made where the process is by placing a dirty bowl in the container so that the bowl will pass one by one to 4 screws which are driven by a dc torque motor which functions for the separation process from the stack. Next, after the bowl reaches the conveyor, it will cross to get to the washing process which is driven by a dc torque motor. The feeder speed can be adjusted using pulse width modulation so it can have variations of speed in the feeder bowl process to get to the washing process. This feeder is able to feed 1411,7 bowl per hour using combination speed of 80 rpm screw motor and 135 rpm conveyor motor.